The Path to Convertibility and Growth : The Tunisian Experience - Bell, Gerwin (Occasional Papers; Occasional Paper ;, 1993)
This paper charts Tunisia's transformation from an inward-looking, heavily regulated economy into a predominantly market- and export-oriented one. The paper highlights some of the major challenges facing the country and draws lessons from Tunisia's experience that can be useful for other countries.